Pengaruh Pemberian Puding Daun Kelor terhadap Status Gizi Pada Balita Gizi Kurang di Wilayah Kerja Puskesmas Simpang Kiri, Aceh Tamiang - Nur Zanah; Yusnaini Yusnaini; Lia Lajuna; Yuni Sari; Evi Zahara (Jurnal Intelek Insan Cendikia, 2026)
Malnutrition among toddlers remains a public health challenge, particularly in areas with limited access to nutritious food. One potential approach to address this issue is the utilization of locally available, nutrient-rich foods such as moringa leaves (Moringa oleifera). This study aimed to analyze the effect of moringa leaf pudding on improving the nutritional status of undernourished toddlers in the working area of UPTD Simpang Kiri Primary Health Center, Aceh Tamiang District. A quasi-experimental design with a pretest and posttest control group was employed. The sample consisted of 30 undernourished toddlers divided into an intervention group (moringa leaf pudding) and a control group (pudding without moringa leaves), with 15 toddlers in each group. The intervention was administered for 14 days. Nutritional status was assessed using the weight-for-age (WFA) Z-score based on WHO standards. Data were analyzed using the Wilcoxon test and the Mann–Whitney U test. The results indicated an increase in average body weight in both groups after the intervention. The Wilcoxon test showed significant differences before and after the intervention in the intervention group (p=0.001) and the control group (p=0.017). However, the Mann–Whitney U test revealed that the difference in nutritional status improvement between the two groups was not statistically significant (p>0.05). In conclusion, moringa leaf pudding did not show a statistically significant effect on improving the nutritional status of toddlers within a 14-day intervention period, although it demonstrates potential as a locally based supplementary food.